Pola Jaringan Distribusi Ikan di Pangkalan Pendaratan Ikan (Ppi) Sodohoa Kota Kendari - Ningsih, Nur Fitria Ningsih; Suyuti, Nasruddin; Aris, La Ode (JURNAL KABANTI: Kerabat Antropologi, 2024)
This research aims to find out and describe the fish distribution network at the Sodohoa Fish Landing Base (PPI) Kendari City as well as knowing and describing the transportation process for distributing fishermen's catches outside the city. The theory used in this research is Zanden Ruddy Agusyanto's theory of Social Networks (1990). Meanwhile, the research method used is an ethnographic method which is carried out by observation and interviews interviews with the aim that the data obtained can be studied in a qualitative descriptive manner. Based on the results of this study, PPI Sodohoa has 5 (five) distribution network strating from, namely involving fishermen, pappalele/bosses, collecting traders, retailers/traveling traders, wholesale traders (fish sellers in various fish markets in Kendari city) , and final consumers (housewives). Among the various forms of distribution, the increasing number of parties involved in the distribution process will certainly increase the price depending on the first hand to the end consumer. The process of transporting fish to distribute fishermen's catches at the Sodohoa Fish Landing Base (PPI) Kendari City, namely the fishermen's catch is handed over to the papalele/boss then sorted based on the type of fish, size of fish and level of freshness of the fish, then put into baskets, after which it is sold to traders fish on PPI. The production of the catch landed at PPI Sodoha, Kendari City, is entirely fish that is still fresh and of good quality. Furthermore, the process of transporting fish out of town is carried out by inter-city traders using cars or trucks and crossing using ferries which will be sent to Makassar and West Sulawesi.